2006
DOI: 10.2193/0084-0173(2006)162[1:pdogsb]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics of Greater Scaup Breeding on the Yukon-Kuskokwim Delta, Alaska

Abstract: Populations of greater scaup (Aythya marila) remained relatively stable during a period when populations of lesser scaup (A. affinis) have declined from historic levels. To assist in describing these differences in population trends, from 1991 through 2000, we studied the survival, nesting ecology, and productivity of greater scaup on the Yukon-Kuskokwim Delta (Y-K Delta), Alaska, to develop a model of population dynamics. We located nests, radio-marked females for renesting studies, estimated duckling surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 45 publications
(106 reference statements)
0
35
1
Order By: Relevance
“…black‐legged kittiwakes, Murphy, Springer & Roseneau ; snow petrels, Chastel, Weimerskirch & Jouventin ; greater scaup, Flint et al . ; black scoters, Schamber, Broerman & Flint ). However, while it is clear that reproductive output in this population is highly variable through time and driven by a complex interplay of environmental factors, the consequences of this variability on population dynamics are not known.…”
Section: Discussionmentioning
confidence: 99%
“…black‐legged kittiwakes, Murphy, Springer & Roseneau ; snow petrels, Chastel, Weimerskirch & Jouventin ; greater scaup, Flint et al . ; black scoters, Schamber, Broerman & Flint ). However, while it is clear that reproductive output in this population is highly variable through time and driven by a complex interplay of environmental factors, the consequences of this variability on population dynamics are not known.…”
Section: Discussionmentioning
confidence: 99%
“…Sea duck species like scoters tend to be relatively long lived (Krementz et al ) and adult survival could have a profound effect on population dynamics, as reported for lesser and greater ( A . marila ) scaup (Flint et al , Koons et al ) and some sea duck species (Mallory ). Thus, filling gaps for these species about sources of variation in adult female survival will provide information about the components that may be controlled by management.…”
Section: Global Climate Indices Anticipated Ecological Effects In Wimentioning
confidence: 99%
“…Ultimately, nesting association (Nudds 1977;Krasowski and Nudds 1986). with larids and subsequent nesting success must be assessed on a site-by-site basis, 1 because larids can serve as a predator of Greater Scaup eggs or they can lessen the effects of other predators (Flint et al 2006). Lastly, an important factor affecting our nesting results was the presence of cattle grazing on Grassy Island during the study period.…”
Section: Discussionmentioning
confidence: 99%